IMPLEMENTATION OF ENVIRONMENTAL ACCOUNTINGAT PT SLJ GLOBAL TBK SAMARINDA - Firmansyah, Wahyu; Ginting, Yoremia Lestari (Universitas Multimedia Nusantara, 2024)
Abstract— This research aims to examine the recognition, measurement, presentation, and disclosure related to waste management activities as a form of environmental accounting at PT SLJ Global Tbk Samarinda. The research utilizes a qualitative research method with descriptive analysis, supported by primary data sources in the form of interview results and secondary data in the form of financial reports and company activities related to waste management. The informants in this research consist of staff from the accounting and safety health environment departments. The results of this research indicate that the recognition, measurement, and presentation are in accordance with environmental accounting and general financial accounting standards. However, there is a lack of detailed disclosure regarding the overall disclosure of fixed asset details, liabilities, and environmental expenses, which have not been conducted in a detailed manner and are not disclosed to the public. Keywords: Environmental Accounting; Financial Accounting.